2016
DOI: 10.1051/0004-6361/201527142
|View full text |Cite
|
Sign up to set email alerts
|

The XXL Survey

Abstract: Context. The XXL Survey is the largest homogeneous and contiguous survey carried out with XMM-Newton. Covering an area of 50 deg 2 distributed over two fields, it primarily investigates the large-scale structures of the Universe using the distribution of galaxy clusters and active galactic nuclei as tracers of the matter distribution. Aims. Given its depth and sky coverage, XXL is particularly suited to systematically unveiling the clustering of X-ray clusters and to identifying superstructures in a homogeneou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Johnston-Hollitt et al 2008;Schirmer et al 2011;Pompei et al 2016;Einasto et al 2015). They are lower than the masses of very rich superclusters such as the Shapley supercluster, the Corona Borealis supercluster, and other very rich superclusters (Reisenegger et al 2000;Proust et al 2006;Ragone et al 2006;Pearson et al 2014;O'Mill et al 2015).…”
Section: Discussion and Summarymentioning
confidence: 96%
See 1 more Smart Citation
“…Johnston-Hollitt et al 2008;Schirmer et al 2011;Pompei et al 2016;Einasto et al 2015). They are lower than the masses of very rich superclusters such as the Shapley supercluster, the Corona Borealis supercluster, and other very rich superclusters (Reisenegger et al 2000;Proust et al 2006;Ragone et al 2006;Pearson et al 2014;O'Mill et al 2015).…”
Section: Discussion and Summarymentioning
confidence: 96%
“…We also added 10% of the total mass as the mass of intercluster gas (see e.g. Pompei et al 2016). Total masses of superclusters M g tot (here g stands for both groups and gas) were obtained by summing these mass estimates.…”
Section: Masses Of Superclustersmentioning
confidence: 99%
“…Early studies reported that AGN are less frequent in galaxy clusters than in the field (Osterbrock 1960;Gisler 1978;Dressler et al 1985) and more recent studies support this suggestion (Kauffmann et al 2004;Popesso & Biviano 2006;von der Linden et al 2010;Pimbblet et al 2013). Other studies, however, have found no differences between cluster and field galaxies (e.g.…”
Section: Introductionmentioning
confidence: 93%
“…all five clusters found at z ∼ 0.43 are located within a circle of 4 radius (1.3 h −1 Mpc) and a sixth but uncertain member within 10 . A more detailed analysis of the supercluster and its BCGs is presented in Pompei et al (2016, hereafter Paper VII). Baran et al (2016, hereafter Paper IX) identified several overdensities via a Voronoi Tessellation analysis of optically detected galaxies and presented new radio observations.…”
Section: Agn In Superclustersmentioning
confidence: 99%
See 1 more Smart Citation